The efect of independent commissioner, related party transactions, and firm leverage on tax avoidance - Firdauzi, Nafisah Aulia; Septiani, Dwi (Educoretax, 2025)
This study investigates the effect of independent commissioners, related party transactions, and firm leverage on tax avoidance in property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Employing a quantitative approach, the study analyzes secondary data from financial statements and annual reports using panel data regression with a common effect model. Based on purposive sampling, 40 firm-year observations are examined. The results show that independent commissioners and related party transactions significantly affect tax avoidance, indicating that internal governance mechanisms and intercompany transactions play a crucial role in shaping corporate tax behavior. Conversely, firm leverage does not influence tax avoidance, suggesting that debt-based tax planning is less relevant in the property and real estate sector. These findings contribute to the tax avoidance literature by providing sector-specific evidence from an emerging market and challenging the dominance of capital structure explanations in corporate tax planning. This study underscores the importance of governance quality and transaction transparency in understanding tax avoidance practices in property and real estate firms.